2016
DOI: 10.1111/jcmm.12795
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin improves the homing of BMSCs via the PI3K/AKT/miR‐9 pathway

Abstract: Bone marrow‐derived mesenchymal stem cells (BMSCs) have great therapeutic potential for many diseases. However, the homing of BMSCs to injury sites remains a difficult problem. Recent evidence indicates that simvastatin stimulates AKT phosphorylation, and p‐AKT affects the expression of chemokine (CXC motif) receptor‐4 (CXCR4). Therefore, simvastatin may improve the expression of CXCR4 in BMSCs, and microRNAs (miRs) may participate in this process. In this study, we demonstrated that simvastatin increased both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…For example, Y. Liu et al () showed that blocking the PI3K–Akt signaling pathway with specific inhibitor LY294002 could decrease the osteogenic inhibitory effect of vaspin as well as the expression level of miR‐34c. Bing et al () suggested that the phosphorylation of AKT affected the expression of miR‐9 expression, while LY294002 increased miR‐9 expression in bone marrow‐derived mesenchymal stem cells. However, our previous study demonstrated that incubating with troxerutin led to the activation of the PI3K–Akt signaling pathway in rat cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Y. Liu et al () showed that blocking the PI3K–Akt signaling pathway with specific inhibitor LY294002 could decrease the osteogenic inhibitory effect of vaspin as well as the expression level of miR‐34c. Bing et al () suggested that the phosphorylation of AKT affected the expression of miR‐9 expression, while LY294002 increased miR‐9 expression in bone marrow‐derived mesenchymal stem cells. However, our previous study demonstrated that incubating with troxerutin led to the activation of the PI3K–Akt signaling pathway in rat cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we have found that MSC transplantation after vein grafting can prevent intimal hyperplasia by accelerating reendothelialization in a rat vein graft model [13,14]. This effect was, in part, attributable to MSCs homed to the site of injury and differentiated into an endothelial phenotype to re-establish the endothelial layer.…”
Section: Introductionmentioning
confidence: 94%
“…All experimental procedures were approved by the Animal Care and Use Committees at Qilu Hospital of Shandong University. The model was carried out using the anastomotic cuff technique as we have described [13,14,17,18]. Briefly, adult Wistar rats were prepared and made intraperitoneal anaesthesia with chloral hydrate.…”
Section: Rat Vein Graft Model and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Translation of stem cells and other regenerative paradigms from bench to bedside requires an understanding of host responses to outside cellular and/or material transplants [1]. Both in vitro and in vivo conditions can influence the cellular behaviours of cellular materials as well as their therapeutic potential following transplantation [2][3][4]. In particular, innate immune responses to transplant-based strategies, especially those arising from macrophages (Mφs), have received much attention in recent years in fields ranging from tissue engineering to in situ tissue regeneration [5,6].…”
Section: Introductionmentioning
confidence: 99%